A multi-view environment to visualize differences between alternative versions of biological taxonomies - Figueroa-Montero, Manuel (Instituto Tecnológico de Costa Rica, 2022)
The classification of living organisms into biological taxonomies is fundamental to understand our biodiversity and to support environmental conservation efforts. The biological taxonomy system for the classification of living organisms was proposed by Carl Von Linné in 1735. Organisms are organized into groups that follow a hi erarchical structure that is composed at least of the following categories: kingdom, phylum, class, order, family, genus and species. Taxonomists work encompasses the identification and classification of species, as well as the registration and mainte nance of the taxonomic records that are kept in museums, herbaria, research centers and institutions dedicated to natural preservation. Those records are constantly changing due to the discovery of new species or the reclassification of the existing ones; therefore, it is common that taxonomists face the challenge of handling large amounts of data that require to be reviewed, compared and corrected. This challenge can be approached through the automatic comparison of the taxonomies. In this work we investigate whether a cluttering reduction approach that visual izes only the differences (VOD) when comparing two alternative versions of a biolog ical taxonomy is more effective than the visualization of the complete taxonomies. We also investigate whether the use of the Coordinated Multiple Views (CMV) technique contributes to a better identification of differences. For this purpose we take as a baseline Diaforá, a novel interactive software that infers and visualizes the differences between two alternative versions of a biological taxonomy by modelling one view only and using the edge-drawing method [52]. We extended Diaforá by integrating CMV and VOD. This research has three stages: 1) the design of two different VOD visualization alternatives, 2) a user study with the goal of evaluating the alternatives and selecting one of them, 3) a final user study that evaluates the original version of Diaforá against one that incorporates the CMV technique with the selected VOD visualization. We found that the proposed model increases significantly the cognitive value of the visualization, making it easier for test subjects to identify the differences between two versions of the classification.

La clasificación de los organismos vivos en taxonomías biológicas es fundamental para comprender nuestra biodiversidad y para apoyar los esfuerzos de conservación del medio ambiente. El sistema de taxonomías biológicas para la clasificación de los organismos vivos fue propuesto por Carl Von Linné en 1735. Los organismos son organizados en grupos que siguen una estructura jerárquica que se compone al menos de los siguientes categorías: reino, phylum, clase, orden, familia, género y especie. El trabajo de los taxónomos consiste en la identificación y clasificación de las especies, así como el registro y mantenimiento de los datos taxonómicos que se conservan en museos, herbarios, centros de investigación e instituciones dedicadas a la preservación natural. Esos registros cambian constantemente debido al descubrimiento de nuevas especies o la reclasificación de las existentes; por lo tanto, es común que los taxónomos enfrenten el reto de manejar grandes cantidades de datos que requieren ser revisados, comparados y corregidos. Este reto se puede abordar mediante la comparación automática de las taxonomías. En este trabajo investigamos si un enfoque de reducción de desorden que visualiza solo las diferencias (VOD) al comparar dos versiones alternativas de una taxonomía biológica es más efectivo que la visualización de las taxonomías completas. También investigamos si el uso de la técnica Coordinated Multiple Views (CMV) contribuye a una mejor identificación de las diferencias. Para este propósito tomamos como base Diaforá, un novedoso software interactivo que infiere y visualiza las diferencias entre dos versiones alternativas de una taxonomía biológica, modelando una sola vista y usando el método de dibujo de bordes [52]. Ampliamos Diaforá integrando CMV y VOD. La investigación constó de tres etapas: 1) el diseño de dos alternativas diferentes de visualización VOD, 2) un estudio de usuario con el objetivo de evaluar las alter nativas y seleccionar una de ellas, 3) un estudio de usuario final que evalúa la versión original de Diaforá frente a uno que incorpora la técnica CMV con la visualización VOD seleccionada. Descubrimos que el modelo propuesto aumenta significativamente el valor cognitivo de la visualización, lo que facilita que los sujetos de prueba hayan podido identificar las diferencias entre dos versiones de la clasificación.
Proyecto de Graduación (Maestría en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2022.
Keywords: Taxonomía; Biodiversidad; Organismos vivos; Conservación del medio ambiente; Mantenimiento -- Datos taxonómicos; Clasificación de especies; Taxonomy; Biodiversity; Living organisms; Conservation of the environment; Species classification; Research Subject Categories::TECHNOLOGY